An industrialized microprocessor system - Block, Gerald (Department of Electrical Engineering, 2016)
The aim of this project is to design and build an industrialized microprocessor system capable of testing the limits and capabilities of microprocessors in the industrial process control world. The system must be capable of operating in a data logging or control or supervisory capacity. The system consists of a ruggerdized, electrically isolated unit, designed on a "black box" principle, with minimum operator controls. It is housed in a sealed crate with internal access via rows of input and output plugs and connecters. The system has been designed on a modular basis in order to simplify expansion. It can be operated as a small dedicated controller or expanded by the addition of memory and/or industrial I/O modules to its full capacity. The system is based on an INTEL 8080 microprocessor. The industrial interface consists of electrically isolated analog and digital input and output modules which can be selected under program control. There are also up to 64 asynchronous priority encoded alarm channels that can interrupt the control sequence at any time should an alarm condition arise. For debugging hardware and software a plug-on front panel unit is provided.